ANALISIS SWOT DALAM MENENTUKAN STRATEGI PEMASARAN PETAK ENAM SEBAGAI DAYA TARIK WISATA KULINER DI KAWASAN GLODOK JAKARTA - Ramadhani, Melly; Narottama, Nararya; Sunarta, I Nyoman (Jurnal IPTA (Industri Perjalanan Wisata); Vol 11 No 1 (2023): Jurnal IPTA (July 2023)DO - 10.24843/IPTA.2023.v11.i01.p11, 2023)
Petak Enam is one of the historical shopping districts in Jakarta, which has now transformed into a renowned Culinary Tourism Attraction (CTA) in Pecinan. To ensure progressive visitor rates, a good marketing strategy is required. This research examines and analyzes both internal and external factors, including strengths, weaknesses, threats, and opportunities of Petak Enam as a culinary tourism center in the capital city, with the aim of obtaining the appropriate marketing strategy. A mixed-method approach is employed to gather quantitative and qualitative data, using direct observation, unstructured interviews, and questionnaire distribution as data collection techniques. This study utilizes SWOT analysis techniques such as IFAS (Internal Factor Analysis Summary), EFAS (External Factor Analysis Summary), and the conclusion of the SWOT Matrix. The research findings indicate that: (1) The marketing strategy employs a synergistic marketing mix; (2) SWOT analysis reveals an aggressive strategy with active promotion, and; (3) Human resource development and facility enhancement are identified as strategies for the development of Petak Enam.